The Role of Foley Catheter Coated with Gold, Silver, and Palladium in Decreasing Urinary Tract Infections in the Intensive Care Unit; a Letter to Editor - Ardehali, Seyed Hossein; Sedaghatmanesh, Maryam; Fatemi, Alireza (Archives of Academic Emergency Medicine, 2019)
Urinary tract infections (UTIs) are among the most common hospital-acquired infections, which are caused by urinary catheterization in most cases (1, 2). These infections, like other hospital-acquired infections, elongate the duration of hospitalization and can act as a depot for antibiotic-resistant bacteria. For each day that the catheter remains in the urinary tract, the probability of UTI increases by 3% to 7% (3). In 2011, the Centers for Disease Control and Prevention (CDC) reported the rate of catheter-related UTI in the intensive care unit (ICU) as 1.2 to 4.5 cases per 1000 catheters per day and the mortality rate related to these infections has been estimated to be about 15% (4).